2021
DOI: 10.3390/rel12070540
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Stigma in Christian Faith Communities: A Qualitative Study

Abstract: Given the increasing numbers of U.S. lives lost to suicide, it is imperative to identify factors that can help protect against suicide. While regular religious service attendance has been found to be protective against suicide, faith communities have taboos against suicide which may be associated with stigma. Nine Christian faith leaders and congregants and one moral psychologist completed interviews on suicide stigma in Christian faith communities. Themes that emerged included internal, interpersonal, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This paper addresses the intersection of three topical areas that have, thus far, received relatively little scholarly attention. While the literature on religion and suicide is vast (for recent reviews, see Lawrence et al 2016;Gearing and Alonzo 2018), as is the literature on the effect of stigma on various mental health problems, including self-killing (e.g., Sudak et al 2008;Clement et al 2014;Schomerus et al 2014;Bernardo and Pinna 2017;Goodwill and Zhu 2020), only a handful of studies have looked at all three aspects simultaneously and examined how negative religious stereotypes affect the risk of self-killing (e.g., van den Brink et al 2018;Caplan 2019;Mason 2021). The research reported in this article seeks to redress this imbalance of attention by using data from a nationwide survey conducted in Hungary.…”
mentioning
confidence: 99%
“…This paper addresses the intersection of three topical areas that have, thus far, received relatively little scholarly attention. While the literature on religion and suicide is vast (for recent reviews, see Lawrence et al 2016;Gearing and Alonzo 2018), as is the literature on the effect of stigma on various mental health problems, including self-killing (e.g., Sudak et al 2008;Clement et al 2014;Schomerus et al 2014;Bernardo and Pinna 2017;Goodwill and Zhu 2020), only a handful of studies have looked at all three aspects simultaneously and examined how negative religious stereotypes affect the risk of self-killing (e.g., van den Brink et al 2018;Caplan 2019;Mason 2021). The research reported in this article seeks to redress this imbalance of attention by using data from a nationwide survey conducted in Hungary.…”
mentioning
confidence: 99%